EFEKTIVITAS SALURAN KOMUNIKASI DALAM MENUNJANG PELAKSANAAN IDENTIFIKASI DAN PENILAIAN RISIKO (Studi Kasus Pada Kantor Akuntansi Publik Gideon Adi & Rekan Surabaya) - Aprilia Intan Nur Aini; Febry Fabian Susanto (Universitas Nusa Cendana, 2026)
This study aims to understand the effectiveness of communication channels in supporting the implementation of risk identification and assessment at the Gideon Adi & Partners Public Accounting Firm in Surabaya. The background of this study is based on the challenges of risk-based auditing, which requires auditors to not only have technical understanding of client entities, but also effective internal coordination within the audit team. This study uses an interpretive qualitative approach with data collection through in-depth interviews with three auditors and a review of internal documents. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the application of vertical and horizontal communication complement each other in strengthening the risk-based audit process.